Community Services and Their Role in Enhancing Urban Resilience - Khotimah, Khusnul; Zakaria, Zakaria; Yendra, Yendra; Tonggiroh, Mursalim (Advances in Community Services Research, 2025)
Purpose: The research aims to comprehensively understand how community services—such as disaster preparedness programs, public health initiatives, and social support systems—fortify urban resilience by addressing diverse urban challenges. Research Design and Methodology: Employing a qualitative research approach, this study conducts an extensive literature review to identify and analyze how community services contribute to urban resilience. The methodology involves thematic analysis and cross-case comparisons to synthesize findings from relevant literature. Findings and Discussion: The findings highlight that community services are pivotal in fostering social cohesion, enabling collective action, and providing essential resources, enhancing communities' capacity to withstand and recover from crises. Disaster preparedness programs improve emergency response and recovery times, while public health initiatives address health-related vulnerabilities and support overall well-being. Social support systems, including welfare programs and housing assistance, mitigate economic hardships and promote social inclusion. Implications: Implications of this study suggest that policymakers and practitioners should focus on enhancing community engagement, investing in community services, and developing innovative models for their integration and sustainability. Future research should explore the long-term impacts of community services on resilience and identify best practices for their implementation across diverse urban contexts.